(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Honey production is a lucrative business, and it generates employment. Kanniyakumari district in Tamilnadu is a pioneer in honey production and the beekeepers depend solely on the flow season for the improving their economic condition. About 10,000 tones of forest honey were produced annually. The primary purpose of this study is to examine the factors influencing honey production and the new techniques adopted by beekeeping that may help in enhancing the productivity and economic growth of the country. The primary and secondary sources of data were utilized for this study. Data were collected from 200 sample respondents that were selected randomly from Kanniyakumari district. The collected data were analyzed using tools like Garrett ranking. To find out the factors influencing honey production, the majority of respondents have ‘prepared honey for sale for further processing’, and the majority of respondents belong to ‘level of income’ for factors affecting the adoption of new technologies in beekeeping, respectively.